2021
DOI: 10.3389/fphys.2021.615175
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Dilatation in Patients With Bicuspid Aortic Valve

Abstract: Bicuspid aortic valve (BAV) is the most common congenital cardiac abnormality. BAV aortic dilatation is associated with an increased risk of adverse aortic events and represents a potentially lethal disease and hence a considerable medical burden. BAV with aortic dilatation warrants frequent monitoring, and elective surgical intervention is the only effective method to prevent dissection or rupture. The predictive value of the aortic diameter is known to be limited. The aortic diameter is presently still the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(7 citation statements)
references
References 151 publications
0
4
0
3
Order By: Relevance
“…Kong et al [ 15 ] demonstrated that the presence of a raphe is of clinical and prognostic importance and is significantly correlated with valve dysfunction and aortic dilation. Most studies have focused on specific BAV morphology according to the orientation of leaflet fusion and the number of commissures [ 1 , 15 ]; however, only a few studies have focused on the presence of a raphe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kong et al [ 15 ] demonstrated that the presence of a raphe is of clinical and prognostic importance and is significantly correlated with valve dysfunction and aortic dilation. Most studies have focused on specific BAV morphology according to the orientation of leaflet fusion and the number of commissures [ 1 , 15 ]; however, only a few studies have focused on the presence of a raphe.…”
Section: Discussionmentioning
confidence: 99%
“…A bicuspid aortic valve (BAV) is the most common congenital heart disease, affecting 0.5% to 2% of the general population [ 1 ]. Although a BAV can be an isolated disorder, it is often associated with serious valvular disorders, including aortic stenosis (AS) and aortic regurgitation (AR), as well as aortic wall abnormalities such as aortopathy, aneurysm, and dissection.…”
Section: Introductionmentioning
confidence: 99%
“…The group had varying degrees and presences of valvular disease as well as different phenotypes of BAVs ( Table 1 ). This could likely lead to an increase in the variability of the results as the different pathoanatomical features of BAVs can correspond to different unfavourable haemodynamic environments [ 55 ].…”
Section: Limitationsmentioning
confidence: 99%
“…Клинические проявления чаще встречаются после 40 лет и демонстрируют свое многообразие [1,4,5,6]. несмотря на то, что у большинства пациентов развиваются такие осложнения, как дисфункция аК и/или дилатация аорты, некоторые из них могут оставаться бессимптомными в течение всей своей жизни.…”
Section: Introductionunclassified